Effect of Zinc Application on Growth, Yield, Zinc uptake and Zinc Use Indices of Rice - Karmakar, Mrinmoy; Sarkar, Narayan Chandra; Shivay, Yashbir Singh; Pramanik, Kalipada (International Journal of Economic Plants, 2024)
A field experiment was conducted at the agriculture farm, Palli Siksha Bhavana, Visva-Bharati, Birbhum, West Bengal, India during kharif (rainy) seasons (June–September) of 2016 and 2017 to study effect of zinc application on growth, yield and nutrient uptake of rice. The experiment was laid out in split plot design replicated thrice, consisting two main plot treatments i.e. crop establishment methods (CEMs) and seven sub-plot treatments (levels of zinc and methods of application). Two CEMs were direct seeded rice (DSR) and transplanted puddled rice (TPR) and seven levels of zinc and methods of application were namely control (Zn0), Seed coating of Zn @ 1250 mg kg-1 (Zn1), Seed coating of Zn @ 2500 mg kg-1 (Zn2), Seed coating of Zn @ 3750 mg kg-1 (Zn3), two foliar sprays @ 1050 mg kg-1 (Zn4), three foliar spray @ 1050 mg kg-1 (Zn5), 2500 mg kg-1 seed coating+2-foliar spray @ 1050 mg kg-1 (Zn6). In respect of yield attribute and yield, Zn6 resulted significantly highest number of Panicle m-2 as well as number of filled grains panicle-1. Zn3 though recorded 5.7% more grain yield than Zn6 but later Zn6 resulted highest zinc concentration and uptake. Zn1 recorded highest zinc use indices. Zn1 resulted much highest Zn use efficiency than foliar application and combined application of seed coating and foliar spray. Correlation between Zn levels and Zn concentration in both grain and straw of rice was highly positive; very highly positive correlation was recorded with the Zn levels and Zn uptake by both grain and straw.